LO19: Should emergency physicians bother offering triptans to patients with acute migraine? A systematic review of parenteral agents. (May 2019) - Visser, L.; Meyer, J.; Kirkland, S.; Villa-Roel, C.; Junqueira, D.; Campbell, S.; Rowe, B.
Abstract : Introduction : Acute migraine headaches are common causes of presentation to the emergency department (ED). There is great variability in the efficacy of the available parenteral agents to manage pain, though triptans are among the recommended treatments. The objective of this systematic review was to update a previous review examining the effectiveness of parenteral agents for the treatment of acute migraine in the ED or equivalent acute care setting; our review examined pain management in emergency settings and assessed the effectiveness of triptan agents.Methods : A comprehensive search of 10 electronic databases and grey literature was conducted to supplement the previous systematic review. Two independent reviewers completed study selection, quality assessment, and data extraction. Any discrepancies were resolved by third party adjudication. Pain scale scores were analyzed using standardized mean difference (SMD) with 95% confidence intervals (CIs) calculated using a random effects model; heterogeneity (I2) was reported.Results : Titles and abstracts of 5039 unique studies were reviewed, of which, 51 studies were included. Sixty-four studies from the original review were included, resulting in a total of 115 included studies. Pain was measured within the ED or equivalent acute care setting using a variety of pain scales, most commonly the 0-10 cm or 100 mm visual analog scale. Four studies compared pain scores between patients receiving sumatriptan vs. other agents, of which, patients receiving sumatriptan reported higher pain scale scores (SMD = 0.53; 95% CI: 0.04, 1.02; I2 = 80%). In particular, patients receiving sumatriptan reported higher pain scale scores than patients receiving metoclopramide (SMD = 0.68; 95% CI: 0.31, 1.04; n = 1) or ketorolac (SMD = 1.39; 95% CI: 0.56, 2.21; n = 1). Overall, studies comparing anti-inflammatory agents (i.e., ketorolac or dexketoprofen) to other agents reported improved pain scale scores among patients receiving anti-inflammatory agents (SMD = -0.38; 95% CI: -0.73, -0.03; I2 = 66%; n = 5).Conclusion : Limited evidence suggests that patients treated with metoclopramide or anti-inflammatory agents experience greater pain reduction compared to patients treated with sumatriptan. This review will conduct a network analysis of parenteral agents to examine the comparative effectiveness of parenteral agents to manage pain among patients with acute migraine. Further analysis will also consider the balance between efficacy and adverse events.